Physiotherapeutic management of a patient with patellofemoral pain syndrome – a case report - Ustarbowska, Katarzyna; Trybulec, Bartosz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Patellofemoral pain syndrome (PFPS) is a disorder of the front compartment of the knee joint with incompletely investigated, probably multifactorial pathogenesis. It mostly affects young people and runners. In patients with PFPS conservative management is a therapy of choice with fundamental importance of physiotherapeutic procedures. Therapy should be highly individualized and considering all possible factors that may cause PFPS symptoms. Aim. The aim of this report was presentation of management of a 23 year old female patient with PFPS that developed secondary to a knee sprain. The medical history, diagnostic and therapeutic procedures were thoroughly described, then obtained results were presented and thereafter discussed. Methods. Clinical assessment included functional and provocative tests of the patellofemoral joint as well as thigh and calf muscles tests, range of motion measurement of the knee joint and pain assessment using the VAS scale. Therapeutic management included 5 sessions of post-isometric muscle relaxation (PIR), mobilizations of the patella and applications of elastic tapes. Results. After 5 sessions of therapeutic management PFPS symptoms were significantly reduced. Pain did not occur during normal activity, whereas in heavy joint loading, it occurred later and was of lower intensity. Range of motion as well as subjective sense of joint stability was also improved. Conclusions. Individually adjusted conservative management based on PIR techniques, mobilizations of patella and kinesiotaping seems to be effective form of therapy for PFPS of functional nature.
Keywords: patellofemoral pain syndrome; excessive lateral pressure syndrome; runner’s knee; physiotherapy; kinesiotaping